К вопросу о структуре множества позиционного поглощения в игровой задаче наведения - Авербух, Ю.В. (Проблемы управления и информатики, 2006)
Вивчаються властивості множини позиційного поглинання в задачі наведення конфліктнокеруючої системи на множину. Показано, що перерізи множини позиційного поглинання в загальному випадку розривно залежать від часу і можуть бути незв’язними навіть у випадку зв’язної цільової множини. The paper is devoted to a problem of conflict controlled system directing on a target set. We study the properties of the positional absorption set. It is shown that the section of positional absorption set depends on the time discontinuously in general case. Also the section of positional absorption set can be disconnected even if the target set is connected.